(untitled) (Annual of the Faculty of Philosophy in Skopje, 2015)
The concepts of “natural” and “supernatural” in the primordial understanding of reality are shown through the points of view of classical authors in the field of the theories on the origin and on the nature of religion (Tylor, Frazer, Durkheim, devons etc.). The grasp of (super)natural forces and the belief in some ontologically dominant existence by the archaic religious men are then outlined in the principles through which their beliefs about their relation with and their position in the world can be summed up. The ideas that homo religious, through a series of ritual acts, thoroughly planned and meticulously controlled, has the capacity to establish a functioning and fruitful relationship with the (super)natural force(s) dominating his world are in the basis of the belief in magic, and also partially of the early forms of religion. The series of magical mimetic actions within the positive cult are outlined through the summaries of Frazer and Mauss and Hubert, and through the similarities and differences between their definitions of the principles of magic.